The Effects of Ambient Charges in a Cournot Duopoly with a Labor-Managed Firm and a Capitalist Firm - Kazuhiro Ohnishi (International Journal of Management, Accounting and Economics)
Non-point sources of pollution include urban runoff, agricultural runoff, sediment from construction sites, and atmospheric deposition of pollutants. Ambient charges as an environmental policy instrument for decreasing non-point source pollution are mainly examined within profit-maximizing oligopoly models. This study considers a Cournot mixed duopoly game model involving a capitalist firm and a labor-managed firm to reevaluate the effects of ambient charges as an environmental policy instrument for mitigating non-point source pollution. The capitalist firm maximizes its overall profit, whereas the labor-managed firm focuses on maximizing profit per worker. The structure of the game is as follows. The government regulator first announces the ambient charge, and then the capitalist firm and the labor-managed firm independently and simultaneously decide their output levels. This study shows that there exists a situation where an increase in the ambient charge can reduce environmental pollution. As a result of the analysis, the study finds that ambient charges could be an effective way to manage non-point source pollution, even in Cournot mixed duopoly.